Synthetic Approaches to Nitro-Substituted Isoxazoles - Vasilenko, Dmitry A.; Sedenkova, Kseniya N.; Kuznetsova, Tamara S.; Averina, Elena B. (Synthesis, 2019)
Nitro-substituted isoxazoles are of utmost interest both as versatile intermediates for targeted organic synthesis and as perspective bioactive compounds for drug development. Nevertheless, the existing approaches to them usually lack generality and strongly depend on the position of the nitro group and on the presence of other substituents in the isoxazole ring. This review provides the first systematization of all available data concerning synthetic approaches to 3-, 4-, and 5-nitroisoxazoles. There are a number of preparative approaches to 4-nitroisoxazoles based on classical heterocyclization reactions of nitro-substituted compounds and the nitration of isoxazoles. 3-Nitro- and, especially, 5-nitroisoxazoles are much less readily available. A few methods affording 3-nitroisoxazoles have been reported, often employing the heterocyclization of unsaturated compounds by treatment with sodium nitrite. The sole general preparative method for 5-nitroisoxazoles, containing a variety of functional groups, employs the heterocyclization of electrophilic alkenes by treatment with tetranitromethane activated with triethylamine.1 Introduction2 Synthesis of 4-Nitroisoxazoles2.1 Nitration of Isoxazoles2.2 Condensations of α-Nitro Ketones or Their Oximes2.3 1,3-Dipolar Cycloaddition of Nitrile Oxides to Acetylenes and Their Synthetic Equivalents2.4 Heterocyclization of Acetylene Derivatives by Treatment with Sodium Nitrite2.5 Heterocyclization of Nitro Derivatives of 1,3-Diketones and Their Synthetic Equivalents2.6 Miscellaneous Methods3 Synthesis of 3-Nitroisoxazoles3.1 Heterocyclization of Acetylene Derivatives or 1,3-Dihalogenoalkenes by Treatment with Sodium Nitrite3.2 Heterocyclization of Morita–Baylis–Hillman Acetates by Treatment with Sodium Nitrite3.3 1,3-Dipolar Cycloadditions4 Synthesis of 5-Nitroisoxazoles4.1 1,3-Dipolar Cycloadditions4.2 Synthesis Using Polynitro Compounds5 Conclusion
Keywords: nitroisoxazoles; nitration; condensation; heterocyclization; cycloaddition; polynitro compounds